MIL-101(Fe)-derived iron oxide/carbon anode for lithium-ion batteries: Derivation process study and performance optimization. (10th September 2022) - Huang, Hui; Cheng, Mingren; Yin, Jiacheng; Zhang, Jijie; Kong, Lingjun; Bu, Xian-He
Highlights: MIL-101(Fe)-derived iron oxide/carbon anode for lithium-ion batteries was prepared by two-step carbonization. The carbonization processes of MIL-101(Fe) and ZIF-67 under N2 were investigated by semi-in situ gas chromatography and in situ powder X-ray diffraction. The prepared iron oxide/carbon anode exhibits a high specific capacity for lithium-ion batteries. Abstract: Metal-organic frameworks (MOFs) have attracted extensive attention due to their tunable porosity and abundant metal ions, making them promising precursors for preparing functional materials for energy storage and conversion. Therefore, a study of their derivatization process is important for designing derivatives with specific functional properties. Herein, MIL-101(Fe) was pyrolyzed to prepare iron oxides/carbon composites, and semi-in-situ gas chromatography and in situ powder X-ray diffraction were used to investigate the derivatization process. When evaluated as a lithium-ion battery anode, MIL-101(Fe)-800–400 prepared by a two-step carbonization process exhibited a higher specific capacity than the material prepared by one-step carbonization under N2 . The reason for the improved electrochemical properties was explored. This work provides a better understanding of the carbonization process of MOFs, which allows the controllable synthesis of other MOF-based functional materials. Graphical abstract: Image, graphical abstract